Factors Affecting Consumers' Comprehensive Vehicle Insurance Policy Purchasing Behavior - Muhammet Kutlu; Serpil Sumer Adin; Hilal Mola; Şeyma Şahin Kutlu (Faculty of Economic and Business, 2024)
Research Originality: With increasing vehicle values in Türkiye and high insurance costs, consumers' vehicle insurance purchasing preferences emerge as a dilemma. The study examines consumers' insurance purchasing behavior in this dilemma's context of risk and overconfidence tendencies.Research Objectives: This study aims to reveal the effects of individual characteristics, attitude toward risk, and overconfidence tendencies on comprehensive vehicle insurance policy purchasing behavior.Research Methods: A questionnaire was administered to 428 selected vehicle owners in Turkey, and the questionnaire results were analyzed using the binary logit model.Empirical Results: The study found that gender, education level, income level, market value of the vehicle, attitude towards risk, and self-confidence level have statistically significant effects on comprehensive vehicle insurance policy purchase decisions.Implications: The relationship between risk-taking behavior, overconfidence, and insurance purchasing behavior requires further discussion. Government policies that increase insurance awareness are recommended to weaken this relationship.JEL Classification: D12, G22, C25How to Cite:Kutlu, M., Sumer Adin, S., Mola, H., & Şahin Kutlu, S. (2024). Analysis of Factors Affecting Consumers' Comprehensive Vehicle Insurance Policy Purchasing Behavior. Etikonomi, 3(2), 539 – 554. https://doi.org/10.15408/etk.v23i2.37807.